2018
DOI: 10.1055/s-0043-123998
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular Docking Studies of (E)-4-(Substituted-benzylideneamino)-2H-Chromen-2-one Derivatives: Entry to New Carbonic Anhydrase Class Of Inhibitors

Abstract: The present article illustrated the synthesis and characterization of a novel series of (E)-4-(substituted-benzylideneamino)-2H-chromen-2-one derivatives 4A-4J: in good to excellent yields. The target compounds were synthesized by refluxing 4-aminocoumarin with aromatic aldehydes in ethanol. The structural confirmation was achieved by spectroscopic techniques such as (H, C-NMR and FT-IR) and elemental analysis. The synthesized compounds were evaluated for carbonic anhydrase II (CA-II) inhibition and free radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The other residues which are present around 3b are Ser1, His2, His3, Trp4, Gly5, His9, Asn10, Gly63, His63, Phe229, and Leu237. Recent literature data also favor our docking results (Fattah et al, ). The 3c ‐receptor docked complex revealed the good conformational state with good interaction pattern within the receptor binding pocket.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The other residues which are present around 3b are Ser1, His2, His3, Trp4, Gly5, His9, Asn10, Gly63, His63, Phe229, and Leu237. Recent literature data also favor our docking results (Fattah et al, ). The 3c ‐receptor docked complex revealed the good conformational state with good interaction pattern within the receptor binding pocket.…”
Section: Resultssupporting
confidence: 88%
“…The ligands-protein binding analyses showed that 3b is confined in the active binding pocket of target protein as mentioned in docking results (Fattah et al, 2018). The 3c-receptor docked complex revealed the good conformational state with good interaction pattern within the receptor binding pocket.…”
Section: Docking Energy and Binding Analysis Of Synthesized Compoundsmentioning
confidence: 75%
See 1 more Smart Citation
“…A large number of sulfonamide‐based carbonic anhydrase inhibitor (CAI) drugs like are in clinical use for more than 70 years as diuretics, antiglaucoma, anticonvulsant, or anti‐infective drugs examples of clinically used CAIs: acetazolamide AZM, methazolamide MZA, ethoxzolamide EZA, dorzolamide DZA, brinzolamide BRZ, zonisamide ZNS, sulpiride SLP, indisulam IND, celecoxib CLX (Figure ) …”
Section: Introductionmentioning
confidence: 99%
“…A large number of sulfonamide-based carbonic anhydrase inhibitor (CAI) drugs like are in clinical use for more Figure 2). [12][13][14] However, due to numerous isoform of carbonic anhydrase enzyme, the search to obtain effective safe drug candidates is still work in progress.…”
Section: Introductionmentioning
confidence: 99%